An Attempt at Assessment of Alnetum Incanae Lüdi 1921 Transformations in the Skawica River Valley (The Beskid Żywiecki MTS) - Skowronek, Izabela; Babczyńska-Sendek, Beata; Chmura, Damian (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2011)
The paper presents an attempt at assessment of Alnetum incanae LÜDI 1921 transformations in the Skawica River valley. The field studies were carried out in the whole Skawica valley. On the basis of phytosociological relevés, the participation of species which prefer riparian habitats, the number and cover of anthropophytes, including invasive plants, were analyzed. The presence of synanthropic sites was also taken into consideration. The research demonstrated that in the study area phytocoenoses of the Alnetum incanae association have primarily retained natural character, in spite of a noticeable influence of human impact. The results suggested that the vicinity of synanthropic sites does not eliminate natural components of phytocoenosis.